Protective Role of rAAV-NDI1, Serotype 5, in an Acute MPTP Mouse Parkinson's Model - Jennifer Barber-Singh; Byoung Boo Seo; Akemi Matsuno-Yagi; Takao Yagi (Parkinson's Disease)
Defects in mitochondrial proton-translocating NADH-quinone oxidoreductase (complex I) have been implicated in a number of acquired and hereditary diseases including Leigh's syndrome and more recently Parkinson's disease. A limited number of strategies have been attempted to repair the damaged complex I with little or no success. We have recently shown that the non-proton-pumping, internal NADH-ubiquinone oxidoreductase (Ndi1) from Saccharomyces cerevisiae (baker's yeast) can be successfully inserted into the mitochondria of mice and rats, and the enzyme was found to be fully active. Using recombinant adenoassociated virus vectors (serotype 5) carrying our NDI1 gene, we were able to express the Ndi1 protein in the substantia nigra (SN) of C57BL/6 mice with an expression period of two months. The results show that the AAV serotype 5 was highly efficient in expressing Ndi1 in the SN, when compared to a previous model using serotype 2, which led to nearly 100% protection when using an acute MPTP model. It is conceivable that the AAV-serotype5 carrying the NDI1 gene is a powerful tool for proof-of-concept study to demonstrate complex I defects as the causable factor in diseases of the brain.